Предмет: Алгебра,
автор: kateshalol
сумма квадратов корней уравнения ax-x^2=a-x равна:
Ответы
Автор ответа:
0
ax-x^2=a-x, х1²+х2² -?
ax-x^2-a+x=0
-x²+ax+x-a=0 *(-1)
x²-ax-x+a=0
x²-(a+1)x+a=0
по т. Виета х1х1=а
х1+х2=а+1
(х1+х2)²=х1²+2*х1х2+х2²=х1²+х2²+2*х1х2
х1²+х2²=(х1+х2)²-2х1х2
(х1+х2)²=(а+1)²=а²+2а+1
х1²+х2²=(х1+х2)²-2х1х2=а²+2а+1-2а=а²+1
х1²+х2²=а²+1.
ax-x^2-a+x=0
-x²+ax+x-a=0 *(-1)
x²-ax-x+a=0
x²-(a+1)x+a=0
по т. Виета х1х1=а
х1+х2=а+1
(х1+х2)²=х1²+2*х1х2+х2²=х1²+х2²+2*х1х2
х1²+х2²=(х1+х2)²-2х1х2
(х1+х2)²=(а+1)²=а²+2а+1
х1²+х2²=(х1+х2)²-2х1х2=а²+2а+1-2а=а²+1
х1²+х2²=а²+1.
Автор ответа:
1
ax-x²=a-x x₁²+x₂²=?
x²-ax+a-x=0
x²-ax-x+a=0
x²-x*(a+1)+a=0
x²-(a+1)*x+a=0
Согласно теоремы Виета:
x₁*x₂=a
x₁+x₂=a+1
(x₁+x₂)²=(a+1)²
x₁²+2x₁*x₂+x₂²=a²+2*a+1
x₁²+2*a+x₂²=a²+2*a+1
x₁²+x₂²=a²+1.
Ответ: x₁²+x₂²=a²+1.
x²-ax+a-x=0
x²-ax-x+a=0
x²-x*(a+1)+a=0
x²-(a+1)*x+a=0
Согласно теоремы Виета:
x₁*x₂=a
x₁+x₂=a+1
(x₁+x₂)²=(a+1)²
x₁²+2x₁*x₂+x₂²=a²+2*a+1
x₁²+2*a+x₂²=a²+2*a+1
x₁²+x₂²=a²+1.
Ответ: x₁²+x₂²=a²+1.
Похожие вопросы
Предмет: Обществознание,
автор: dk6677776
Предмет: Литература,
автор: yurasirov245
Предмет: Геометрия,
автор: klimtsev06
Предмет: Математика,
автор: Jane111111111
Предмет: Математика,
автор: sashkauz